Bacterial biofilms: a possible mechanism for chronic infection in patients with lumbar disc herniation – a prospective proof‐of‐concept study using fluorescence in situ hybridization. Issue 5 (25th April 2018) - Ohrt‐Nissen, Søren; Fritz, Blaine G.; Walbom, Jonas; Kragh, Kasper N.; Bjarnsholt, Thomas; Dahl, Benny; Manniche, Claus
Abstract : A relationship has been suggested between lumbar disc herniation (LDH) and chronic bacterial infection frequently involving Propionibacterium acnes, which is known to cause chronic infection through the formation of biofilm aggregates. The objective of the study was to assess whether a disc infection involving biofilm formation is present in patients with LDH. A total of 51 LDH patients and 14 controls were included. Bacterial DNA was detected by real‐time polymerase chain reaction (PCR) in 16/51 samples in the LDH group and 7/14 controls (p = 0.215). Sequencing identified bacteria in 9/16 and 6/7 PCR positive samples in the LDH and control groups, respectively. All samples were stained using fluorescence in situ hybridization (FISH) and examined by confocal laser scanning microscopy. Microscopy demonstrated tissue‐embedded bacterial aggregates with host inflammatory cells in 7/51 LDH patients and no controls. The presence of both bacterial aggregates and inflammatory cells suggests a chronic infection in a subset of LDH patients. The finding of bacterial 16S rDNA in both LDH and control disc tissue highlights the importance of microscopic observation to discriminate infection vs contamination. Our findings may have therapeutic implications, as the treatment of biofilm infections is different and more challenging than traditional infections.